The association between anthropometric measures and lung function in a population-based study of Canadian adults. (October 2017) - Rowe, A.; Hernandez, P.; Kuhle, S.; Kirkland, S.
Abstract: Background: Decreased lung function has health impacts beyond diagnosable lung disease. It is therefore important to understand the factors that may influence even small changes in lung function including obesity, physical fitness and physical activity. The aim of this study was to determine the anthropometric measure most useful in examining the association with lung function and to determine how physical activity and physical fitness influence this association. Methods: The current study used cross-sectional data on 4662 adults aged 40–79 years from the Canadian Health Measures Survey Cycles 1 and 2. Linear regression models were used to examine the association between the anthropometric and lung function measures (forced expiratory volume in 1 s [FEV1 ] and forced vital capacity [FVC]); R 2 values were compared among models. Physical fitness and physical activity terms were added to the models and potential confounding was assessed. Results: Models using sum of 5 skinfolds and waist circumference consistently had the highest R 2 values for FEV1 and FVC, while models using body mass index consistently had among the lowest R 2 values for FEV1 and FVC and for men and women. Physical activity and physical fitness were confounders of the relationships between waist circumference and the lung function measures. Waist circumference remained a significant predictor of FVC but not FEV1 after adjustment for physical activity or physical fitness. Conclusions: Waist circumference is an important predictor of lung function. Physical activity and physical fitness should be considered as potential confounders of the relationship between anthropometric measures and lung function. Highlights: SF5 was the anthropometric measure leading to the highest R 2 values in models predicting both FEV1 and FVC- BMI (body mass index) was the anthropometric measure leading to the lowest R 2 value in models predicting both FEV1 and FVC. Physical fitness/activity were confounders of the relationship between WC and both FEV1 and FVC. Upon adjusting FVC models for physical fitness/activity, WC remained a significant predictor. Upon adjusting FEV1 models for physical fitness/activity, WC was no longer a significant predictor.